Gender Equality in the Household Life of Generation Z - Wiranti, Wiranti; Abadi, Lukman Trijaya; Rahman, Zaizul bin Ab (al-Rasῑkh: Jurnal Hukum Islam, 2025)
Generation Z has grown up in the digital era with broad access to information, including discourses on gender equality. In the context of family relationships, this generation demonstrates a shift in values and practices compared to previous generations. This study aims to explore how Generation Z couples perceive and practice gender equality within the household. The research employs a descriptive qualitative method with a phenomenological approach, using in-depth interviews with married Generation Z couples. The findings reveal that these young couples exhibit a relatively high awareness of gender equality principles, as reflected in a more balanced distribution of domestic roles and childcare responsibilities. Women tend to be more vocal in expressing their expectations for equality, while men show a degree of openness to shifting traditional gender roles, although patriarchal values still exert significant influence. The study concludes that gender equality practices among Generation Z couples have made substantial progress, yet continue to face challenges through ongoing negotiations with deeply rooted cultural norms. This research recommends further studies with broader participant diversity and interdisciplinary approaches to capture the long-term dynamics of gender equality within modern family relationships.